2018
DOI: 10.1007/s13300-018-0381-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Glargine Combined with Oral Antidiabetic Drugs for Asians with Type 2 Diabetes Mellitus: A Pooled Analysis to Identify Predictors of Dose and Treatment Response

Abstract: IntroductionIn Asia, patients with type 2 diabetes mellitus (T2DM) often have suboptimal glycemic control for many years prior to initiating basal insulin. Active titration of basal insulin is also required to improve glycemic outcomes. This pooled analysis was conducted to determine the impact of patient baseline covariates on the required dose of basal insulin and treatment response, for the improved management of Asian patients with T2DM.MethodsData on insulin-naïve Asian patients with T2DM who initiated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The pooled analysis showed that higher doses of glargine are likely to be required in patients with higher baseline BMI or FPG in both Asian and Chinese populations. 17 The Asian Treat to Target Lantus Study(ATLAS) is designed to compare the effectiveness of a patient's-versus physician's-led titration of insulin glargine-based basal insulin management in the specific setting of Asia. A total of 161 Chinese patients were randomized 1:1 to the above two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled analysis showed that higher doses of glargine are likely to be required in patients with higher baseline BMI or FPG in both Asian and Chinese populations. 17 The Asian Treat to Target Lantus Study(ATLAS) is designed to compare the effectiveness of a patient's-versus physician's-led titration of insulin glargine-based basal insulin management in the specific setting of Asia. A total of 161 Chinese patients were randomized 1:1 to the above two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because of interethnic differences in the pathophysiology of T2D and its high prevalence in Asian populations, it is important to study the effects of antihyperglycemic therapies in Asian patients. Three recent publications have reviewed and/or analyzed previously reported IGlar treatment results in Asian patients from multiple RCTs or from a combination of RCTs and real-world data [ 42 44 ]. These studies suggest the need for timely initiation of basal insulin [ 42 , 44 ] or a combination of basal insulin/prandial therapy (i.e., incretin mimetics or rapid-acting insulin) [ 43 ] in Asian patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…3 Insulin glargine belonging to the insulin group of drugs, is one of the important baseline insulin sub types used in IDDM (insulin dependent diabetes mellitus), certain select cases of NIDDM (non-insulin dependent diabetes mellitus) and certain specific clinical situations in diabetes management. 4,5 It is used as a baseline insulin preparation which covers the daily baseline requirement of insulin in the patient. It is used along with bolus insulin preparations or oral drugs.…”
Section: Introductionmentioning
confidence: 99%